(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Overtime, interest has risen in museum research, with researchers finding answer to issues such as visitors experience, visitors’ interest, visitors need, motivations and desire to revisit. Lighting in museum is one of many crucial factors in museum finishing, that could motivate, promote or discourage more visit by tourists. The intensity of the spatial lighting could be excessive, or not sufficient. The understanding of lighting being sourced primarily from daylighting, and supported with artificial lighting, especially to serve as energy sources for the rainy seasons and the night hours in many parts of the world is a vital design criterion especially in Nigeria. Museum design over time has held on to the philosophy of putting out completely the natural light in museum design, or relegating it to common spaces in the museum such as circulation areas. Research has shown that the essence of natural lighting to the human psychology is very important, for effective productivity within spaces, which includes the museum, which double function today as a learning space too. This research is a step further in emphasizing this importance, and addressing the problem of balance between natural and artificial lighting within the museum exhibition space, to protect artifacts on display and promote maximum productivity amongst tourist and space users of a museum, thereby enhancing cultural tourism. For the purpose of this research, qualitative method of data collection is employed, using case study as the primary source for data collection, aside interview, and literatures for secondary data. Findings show that natural lighting in a museum can be controlled and adequately regulated using strategies such as building orientation with openings in the north and south axis of the site, strategic openings which promote in-direct contact with artifacts on display, treated glazing such as the anti-solar glass, and use of filters on glasses to keep the harmful UV ray out of the indoor space, and use of recesses and shading devices. The, research will enhance museum experience, through lighting within the museum space, and recommends proper control strategies for natural lighting, to enhance visitor’s performance, protect the artifacts on display, and enhance cultural tourism.